2017
DOI: 10.1108/ijem-11-2015-0158
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors influencing international students’ decision to choose a higher education institution

Abstract: Purpose There is little research into small higher education institutions and international students’ choice in selecting these institutions. The purpose of this paper is to understand the factors that influence international student choices in selecting a small institution. In particular, this study compares the differences between Chinese students and other international students in selecting an institution, specifically based on sources of information used, usefulness of the information, pull motivations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 45 publications
1
55
2
Order By: Relevance
“…Thus, they can get to know Unsoed, trust, and can introduce Unsoed to international community. Increased inbound and outbound flows can show that the university can be trusted by international audiences because International student mobility is an important cornerstone of internationalization around the world (MacEachern & Yun, 2017). In addition, providing more scholarships for foreign students is necessary to increase international trust through inbound students although it is costly.…”
Section: Offering Scholarships For Foreign Studentsmentioning
confidence: 99%
“…Thus, they can get to know Unsoed, trust, and can introduce Unsoed to international community. Increased inbound and outbound flows can show that the university can be trusted by international audiences because International student mobility is an important cornerstone of internationalization around the world (MacEachern & Yun, 2017). In addition, providing more scholarships for foreign students is necessary to increase international trust through inbound students although it is costly.…”
Section: Offering Scholarships For Foreign Studentsmentioning
confidence: 99%
“…Extant research in the context of Chinese students studying overseas has revealed push factors that include the value of obtaining a foreign degree and the high level of competition for obtaining a domestic university degree. Regarding the quality of higher education, the driving factor is that institutions in other countries provide better learning conditions than domestic providers [ 21 , 22 ]. Environmental factors push Chinese residents to send their children to study abroad at a lower level of education and adapt to the natural and social environment abroad at a young age.…”
Section: Discussionmentioning
confidence: 99%
“…There are many factors that affect international students' decisions to study abroad and their particular destination choices. The push-pull model has prevalently been used as a framework in previous research to explain international students' decisions on their study abroad destinations (Gong & Huybers, 2015;James-MacEachern & Yun, 2017;Mazzarol & Soutar, 2002). Mazzarol and Soutar (2002), for instance, conducted three surveys among students from four Asian countries to examine the factors that affected students' choice of a host country.…”
Section: The Push-pull Model and Preference For American Universitiesmentioning
confidence: 99%